Single‐Cell Metabolic Labeling Probe for Diagnosing Tuberculous Meningitis: A Case Report - Jiahao Wang; Guiqin Dai; Pengfei Zhao; Mingbin Zheng; Li Wei; Hongzhou Lu (iLabmed)
ABSTRACT Tuberculous meningitis (TBM), an extrapulmonary form of tuberculosis (TB), is characterized by low bacterial load and lacks efficient diagnostic techniques, often leading to delayed diagnosis and high rates of mortality and disability. We present a case highlighting the superior performance of a single‐cell metabolic labeling probe for tuberculosis (SCMLP‐TB) in achieving rapid and accurate diagnosis of TBM. A 16‐year‐old girl had a 2‐month history of refractory fever and worsening headache. Brain magnetic resonance imaging showed slightly abnormal signals in the right frontal lobe sulci. Standard diagnostic methods such as acid‐fast staining, mycobacterial culture, and cerebrospinal fluid analysis all yielded negative results. SCMLP‐TB successfully detected Mycobacterium tuberculosis in cerebrospinal fluid within 2 h in this case of clinically suspected TBM. Metagenomic next‐generation sequencing later confirmed this finding. An anti‐tuberculosis four‐drug fixed‐dose combination regimen was initiated on day 7 of hospitalization, resulting in gradual symptom and radiological improvement after 8‐month follow‐up. This first clinical application of the SCMLP‐TB technology for diagnosing TBM underscores its value in point‐of‐care testing for paucibacillary TB infection.